Improving the professional training of music culture teachers - Mustafayev, Bakhtiyor Ibragimovich (Goodwood Publishing, 2024)
Purpose: This study examines strategies for improving the professional training of Music Culture teachers in Uzbekistan by strengthening theoretical knowledge, pedagogical competence, and emotional intelligence to respond to modern educational reforms and cultural development. Research Methodology: A qualitative–descriptive approach was employed through the analysis of normative documents, pedagogical literature, and best practices in teacher education. Comparative reviews of international studies and empirical findings on teacher self-efficacy, emotional intelligence, and practicum design were integrated to construct a comprehensive analytical framework. Results: The findings reveal that many Music Culture teachers experience weak theoretical foundations, low self-efficacy, and elevated teaching anxiety, which negatively affect classroom performance. Evidence indicates that competency-based practicums, the integration of signature pedagogy through digital platforms, and emotional intelligence training significantly enhance professional competence, creativity, and resilience. Continuous professional development focusing on both theoretical literacy and practical skills further strengthens teachers’ capacity to deliver high-quality music education. Conclusions: Effective professional training requires an integrative system combining musical performance, theoretical mastery, and pedagogical innovation. Addressing psychological dimensions such as emotional intelligence and self-efficacy is equally essential for sustainable professional growth. Limitations: This study focuses on secondary school teachers in Uzbekistan, limiting its broader applicability. In addition, its conceptual nature requires further empirical validation. Contribution: This study offers a holistic model for teacher training that integrates musical expertise, pedagogical competence, and emotional development, supporting educational policy and curriculum reform and positioning Music Culture teachers as both educators and cultural ambassadors.